A new complication registration system for errors in radiology: Initial 5-year experience in a tertiary care radiology department. Issue 130 (September 2020) - Carrara, Marco; Yakar, Derya; Kasalak, Ömer; Kwee, Thomas C.
Highlights: A new radiologic complication registration system was introduced in this study. Implementation of this new system in clinical practice proved feasible. Its yield in a tertiary care radiology department was described. Abstract: Purpose: To describe and evaluate our initial 5-year experience with a new complication registration system for errors in radiology. Materials and methods: This study reviewed all cases that were submitted to a new complication registration system of a tertiary care radiology department between 2015–2019. Results: Sixty-seven cases were included. In the group of diagnostic complications/errors (n = 34), there were 21 perceptual errors and 13 cognitive errors. This 61.8 % (21/34) perceptual error rate was not significantly different ( P  = 0.297) from the 70 % perceptual error rate known from previous literature. In the group of interventional complications (n=19), most cases (47.4 % [9/19]) concerned symptomatic or major hemorrhage. In the group of organizational complications/errors (n=14), the leading incident type according to the International Classification System for Patient Safety was clinical process/procedure with wrong body part/side/site as subclassification (35.7 % [5/14]). Harm severities were none (n=35), mild (n=10), moderate (n=10), severe (n=6), death (n=5), and unknown (n=1). Harm severity of interventional complications was significantly higher ( P  < 0.05) than that of organizational complications, while there were no significant differences in harm severities between other groups of complications. Conclusion: It is feasible to implement the radiologic complication registration system that was described in this study. Perceptual mistakes, hemorrhage, and procedures on the wrong body part/side/site dominated in the categories of diagnostic, interventional, and organizational complications/errors, respectively, and these should be the topic of vigilance in clinical practice and further research. Future studies are also required to determine whether this complication registration system reduces radiologic errors and improves healthcare quality.